2011
DOI: 10.1002/anie.201100115
|View full text |Cite
|
Sign up to set email alerts
|

Micromachine‐Enabled Capture and Isolation of Cancer Cells in Complex Media

Abstract: Microrockets detect cancer: A micromachine is used for the in vitro isolation of pancreatic cancer cells in complex media. The strategy is based on the selective binding and transport ability of antibody‐functionalized microengine rockets: these microrockets selectively recognize the surface antigens overexpressed by pancreatic cancer cells, and capture and transport the cancer cells over a preselected path (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
367
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 397 publications
(375 citation statements)
references
References 26 publications
3
367
1
4
Order By: Relevance
“…The signicant reduction in the motor speed in serum samples reects their high viscosity, 24 and is consistent with the behavior observed in previous studies. 12,13,15,16 Overall, these results clearly indicate that although the real sample matrix has a signicant effect on the microengine velocity (with higher speed diminutions upon increasing the complexity of the matrix), polymer-based microtube engines can move efficiently at relatively high speeds in a broad spectrum of uids. We attribute the favorable propulsion of polymer-based microtube engines in diverse raw real samples, compared to the greatly hindered motion reported recently for Cu-Pt microjets, 19,20 to their optimal geometry, well dened shape, large opening and light weight.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…The signicant reduction in the motor speed in serum samples reects their high viscosity, 24 and is consistent with the behavior observed in previous studies. 12,13,15,16 Overall, these results clearly indicate that although the real sample matrix has a signicant effect on the microengine velocity (with higher speed diminutions upon increasing the complexity of the matrix), polymer-based microtube engines can move efficiently at relatively high speeds in a broad spectrum of uids. We attribute the favorable propulsion of polymer-based microtube engines in diverse raw real samples, compared to the greatly hindered motion reported recently for Cu-Pt microjets, 19,20 to their optimal geometry, well dened shape, large opening and light weight.…”
mentioning
confidence: 82%
“…[9][10][11] Previous studies have also indicated the facile motion of polymer-based micromotors or rolled up microjets in various diluted (3-4 fold diluted) real-life media. [12][13][14][15][16][17][18] However, recent reports claimed that the movement of bubble-propelled Cu-Pt microengines is greatly hindered in various diluted real samples, and even completely stopped in highly diluted serum or seawater. 19,20 Such observations may have profound implications on the scope of future applications of microscale machines.…”
mentioning
confidence: 99%
“…Because microjets rely on fuel ingression into a tubular structure, these examples are highly sensitive to surface tension and need the addition of surfactants in order to decrease the surface tension and allow fuel ingression. [ 14,[46][47][48][49][50][51][52][53][54] Likewise, the majority of the reported spherical micromotors either need addition of a surfactant in order to achieve propulsion, [ 6,7,10,55,56 ] or alternatively propulsion has only been demonstrated in a specifi c non-aqueous solvent system. For some of these examples, biocompatibility was also specifi cally assessed by measuring motion within fl uids such as serum, and again surfactants were required in order for motion to be produced.…”
mentioning
confidence: 99%
“…[32,33] These new US-triggered, PFC-loaded microbullets can travel at remarkably high average velocities (~6.3 m s −1 : over 100 times faster than currently published micromachines) [11][12][13][14] and deeply penetrate and deform kidney tissue. The concomitance of powerful MB propulsion, biocompatible PFC emulsion fuel, [35] and deeply penetrative, yet medically safe US [34] could lead to highly targeted in vivo drug delivery, artery cleaning, gene regulation schemes, and cancer therapeutics that require higher specificity and accuracy than the current state-of-the-art.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] A wide variety of chemically-powered and magnetically-propelled micro/nanoscale machines have been developed for specific biomedical applications ranging from lab-on-chip bioanalytical devices to site-specific drug delivery targeting. However, these micro/ nanomachines lack the power and biocompatibility necessary for penetrating tissue and cellular barriers, for in vivo cargo delivery and precision nanosurgery.…”
Section: Introductionmentioning
confidence: 99%